Black triangle이 존재하지 않는 보존적이고 심미적인 상악 정중이개의 치료 - 정경화(Kyoung-Hwa Jung); 권은영(Eun-Young Kwon); 최윤경(Youn-Kyung Choi); 김소연(So-Yeun Kim); 전혜미(Hye-Mi Jeon); 박정길(Jeong-Kil Park) (Journal of dental rehabilitation and applied science, 2017)
Anterior diastemas are common esthetic problems. One of the challenges in clinical esthetic dentistry is closing anterior diastemas without creating "black triangles" between the teeth. The success of a restorative treatment in anterior teeth depends on the esthetic integration between soft tissues and hard tissues. This report describes the successfully accomplished diastema closure case by producing the emergence profile with natural contours at the gingival-tooth interface and then generating of gingival recontouring process. 전치부에 발생한 치간이개는 심미적으로 문제를 일으키는 흔한 원인이 된다. "Black triangle"을 생성시키지 않고 치간이 개를 폐쇄시키는 것은 심미치과학에서 도전적 과제 중 하나이다. 전치부 수복치료의 성공 여부는 연조직과 경조직간의 심미적인 연합에 달려있다. 이번 증례에서는 치은-치아 계면에서 자연스러운 외형을 가지는 출현윤곽(emergence profile)을 형성하여 줌으로써 치은의 재생 과정이 일어나 심미적으로 만족스러운 치간이개 폐쇄를 이루어내었기에 이를 보고하는 바이다.